A homozygous nonsense mutation in DCBLD2 is a candidate cause of developmental delay, dysmorphic features and restrictive cardiomyopathy - Kheloud M. Alhamoudi (Nature Portfolio, 2021)
Abstract DCBLD2 encodes discodin, CUB and LCCL domain-containing protein 2, a type-I transmembrane receptor that is involved in intracellular receptor signalling pathways and the regulation of cell growth. In this report, we describe a 5-year-old female who presented severe clinical features, including restrictive cardiomyopathy, developmental delay, spasticity and dysmorphic features. Trio-whole-exome sequencing and segregation analysis were performed to identify the genetic cause of the disease within the family. A novel homozygous nonsense variant in the DCBLD2 gene (c.80G > A, p.W27*) was identified as the most likely cause of the patient’s phenotype. This nonsense variant falls in the extracellular N-terminus of DCBLD2 and thus might affect proper protein function of the transmembrane receptor. A number of in vitro investigations were performed on the proband’s skin fibroblasts compared to normal fibroblasts, which allowed a comprehensive assessment resulting in the functional characterization of the identified DCBLD2 nonsense variant in different cellular processes. Our data propose a significant association between the identified variant and the observed reduction in cell proliferation, cell cycle progression, intracellular ROS, and Ca2 + levels, which would likely explain the phenotypic presentation of the patient as associated with lethal restrictive cardiomyopathy.